Relationship between knowledge and adolescent social environment with inhalation abuse (fox glue) - Losita, Devi Anna; Damayanti, Rika (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study was to determine the relationship between knowledge about the dangers of inhalationand the social environment of adolescents to the abuse of Fox glue. This study used a Cross-Sectional Design experimental design. The research subjects used in this study were 64 adolescents in the Pidada Panjang village, Bandar Lampung. Selection of subjects using simple random sampling technique by taking samples from members of the population at random without considering the existing strata. In this study, using data collection techniques with three instruments, the first instrument is knowledge of inhalation hazards (Asti, 2014), the second instrument is the influence of the social environment (Hidayat, 2016), and the third instrument of inhalation abuse changed by the researchers themselves. The data analysis technique used was Univariate and Bivariate. The results showed that there was a relationship between knowledge about the dangers of inhalation (p-value = 0.003) and the social environment of adolescents (p-value = 0.000) on the abuse of Fox glue. The findings of this study prove that knowledge about the dangers of inhalation and the social environment is related to the prevention of inhalation abuse (Fox glue) in adolescents. The higher the knowledge about the dangers of inhalation and a good social environment, the higher the preventive measures against inhalation (Fox glue)